2003
DOI: 10.1097/01.asn.0000060682.25472.c3
|View full text |Cite
|
Sign up to set email alerts
|

Menopause and Postmenopausal Hormone Use and Risk of Incident Kidney Stones

Abstract: Abstract. Menopause is associated with increased urinary calcium excretion, which could increase the risk for the development of calcium-containing kidney stones. However, it is unknown whether menopause and postmenopausal hormone (PMH) use are independent risk factors for incident kidney stone disease in women. Data from 91,731 female Nurses' Health Study participants who provided information on diet, menopause status, and kidney stone disease were used to examine the independent association between menopause… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
26
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(29 citation statements)
references
References 28 publications
3
26
0
Order By: Relevance
“…These results are in agreement with Mattix Kramer et al28 who reported that ovariectomized rats had impaired calcium balance that could have contributed to ovariectomy-induced OP. Menopause is associated with impaired intestinal calcium absorption that could be attributed to reduced plasma 1,25 dihydroxy vitamin D levels, as well as to the resistance of the gastrointestinal system to the action of 1,25 dihydroxy vitamin D 29.…”
Section: Discussionsupporting
confidence: 93%
“…These results are in agreement with Mattix Kramer et al28 who reported that ovariectomized rats had impaired calcium balance that could have contributed to ovariectomy-induced OP. Menopause is associated with impaired intestinal calcium absorption that could be attributed to reduced plasma 1,25 dihydroxy vitamin D levels, as well as to the resistance of the gastrointestinal system to the action of 1,25 dihydroxy vitamin D 29.…”
Section: Discussionsupporting
confidence: 93%
“…Since menopause is associated with increased urinary calcium excretion, it may have confounded the results. 12 There was no correlation between changes in serum 25(OH)VD levels and urinary calcium excretion (r = 0.032, p = 0.857) (Fig. 3).…”
Section: Discussionmentioning
confidence: 86%
“…We found a significant increase in overweight and obese individuals in the studied period (+20.6%). A previous study preformed by Taylor et al determined that body size is independently associated with the development of kidney stones (15). The authors showed a relative risk of kidney stones in obese men to be 1.33 vs that in normal weight men, whereas in obese women the risk was up to 2.09 times higher than in normal weight women.…”
Section: Discussionmentioning
confidence: 99%